1978
DOI: 10.1210/endo-103-1-281
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-Releasing Hormone Release from the Rat Hypothalamus: Dependence on Membrane Depolarization and Calcium Influx*

Abstract: Release of gonadotropin-releasing hormone (GnRH) was studied by incubating individual rat hypothalami for 60 min, after a 30-min preincubation period, and measuring GnRH in the medium by immunoassay. During the 1 h of incubation, endogenous GnRH release was linear and exogenous GnRH was not destroyed. Membrane depolarization produced by increasing the medium potassium concentration to 60 mM increased GnRH release to 200-500% of control. Membrane depolarization produced by adding 10(-5) or 10(-4) M ouabain incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
21
1

Year Published

1979
1979
2000
2000

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 19 publications
3
21
1
Order By: Relevance
“…We have recently described a hypothalamic incubation system that offers the possibility of investigating the factors that regulate GnRH secretion (6). GnRH release into the incubation medium in this system is linear for 1 h; stimulated by membrane-depolarizing concentrations of potassium and ouabain; and is inhibited by omitting calcium from the incubation medium or by blocking calcium uptake with verapamil.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently described a hypothalamic incubation system that offers the possibility of investigating the factors that regulate GnRH secretion (6). GnRH release into the incubation medium in this system is linear for 1 h; stimulated by membrane-depolarizing concentrations of potassium and ouabain; and is inhibited by omitting calcium from the incubation medium or by blocking calcium uptake with verapamil.…”
Section: Discussionmentioning
confidence: 99%
“…GnRH release in the hypothalamic incubation system employed here has been shown to depend on membrane depolarization and calcium uptake (6) Incubation. Hypothalami were removed and incubated as described (6). The hypothalami were placed, one per tube, in incubation medium at 37°C.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Glutamergic and noradrenergic terminals stimulate the NOergic neuron to release NO by action on their receptors to increase intracellular free calcium in the NOergic neurons, and the calcium combines with calmodulin that activates neural NO synthase (NOS), causing synthesis and release of NO from the neurons. Previous experiments have shown that LH-RH is released from medial basal hypothalamic explants by membrane depolarization by high potassium concentrations [K ϩ ] (24,25), by the specific stimulant Nmethyl-D-aspartate (NMDA) (26)(27)(28)(29)(30)(31)(32), and by a releaser of NO, nitroprusside (NP) (18,26,30,33), whereas inhibition of NO synthesis with the competitive inhibitor of the enzyme N Gmonomethyl-L-arginine (NMMA) blocked NMDA-induced stimulation of LH-RH release, indicating the crucial role of NO in the response.…”
mentioning
confidence: 99%
“…Prostaglandin E2 (PGE2) stimulates the release of luteinizing hormone-releasing hormone (LH-RH) from hypothalamic tissue incubated under in vitro conditions (1)(2)(3)(4)(5), and this stimulation has a partial requirement for the influx of extracellular calcium (1,6). Several lines of evidence strongly suggest that, as in other secretory cells, calcium influx coupled to an increase in the intracellular levels of cAMP serve as a major intracellular pathway mediating PGE2 action on the LH-RH neuron or on other neurons, the secretory products of which stimulate LH-RH release.…”
mentioning
confidence: 99%